2014
DOI: 10.1007/s10973-014-4259-4
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of ‘thiourea urea magnesium chloride’ and ‘urea thiourea sodium chloride’

Abstract: Gopinath et al. report to have grown single crystals of thiourea urea magnesium chloride (1) (J Therm Anal Calorim 2012, 109:841-5) and urea thiourea sodium chloride (2) (J Therm Anal Calorim 2012, 110:789-92) from an aqueous solution containing thiourea, urea and magnesium chloride (sodium chloride for 2) by the slow evaporation method. In this letter, it is proved that (1) and (2) are not new metal-thiourea compounds but pure thiourea. In view of no chemical reaction among the reagents employed for crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…To avoid use of such nonstandard codes, compounds are referred to by numbers in this comment. In recent papers, we have highlighted on the importance of reporting the molecular formula for new compounds [4][5][6]. In this letter, we show the usefulness as well as limitations of unit cell data for characterization of new compounds, using the title compounds as examples.…”
Section: Commentmentioning
confidence: 90%
See 1 more Smart Citation
“…To avoid use of such nonstandard codes, compounds are referred to by numbers in this comment. In recent papers, we have highlighted on the importance of reporting the molecular formula for new compounds [4][5][6]. In this letter, we show the usefulness as well as limitations of unit cell data for characterization of new compounds, using the title compounds as examples.…”
Section: Commentmentioning
confidence: 90%
“…In accordance with the formation of thiourea, the reported infrared spectra of 1 and 2 perfectly match with the IR spectrum of pure thiourea. A similar proof based on IR spectrum has been recently used to show that the so-called thiourea urea magnesium chloride and urea thiourea sodium chloride are actually thiourea [4]. For compound 3, the authors did not report any unit cell data.…”
Section: Commentmentioning
confidence: 98%
“…Based on the IR spectrum, it can be concluded that the name 'urea thiourea cadmium sulfate' is inappropriate for the UTCS crystal. The same criterion namely the absence of the C=O vibration was used as evidence to prove the dubious nature of five other improperly characterized compounds (Table 1) claimed to contain both urea and thiourea [2][3][4].…”
mentioning
confidence: 99%